THE EFFECT OF GIVING FE TABLET AND AMBON BANANA ON INCREASING HEMOGLOBIN LEVELS OF THIRD TRIMESTER PREGNANCY WOMAN WITH ANEMIA - Fauzia, Lilia; Aliefia Meta Duwairoh; Dwi Kurnia (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Introduction : Anemia in pregnancy is the condition of the mother with Hb levels below 11 g% in the first and third trimesters or levels < 10.5 g% in the second trimester. The aim is to give tablets of Fe and Ambon bananas to increase hemoglobin levels in pregnant women with anemia in the third trimester. Metode : Analytical design approach Quasy Experiment, the independent variables are Fe tablets and Ambon banana, dependent on the increase in hemoglobin levels. The population of pregnant women with anemia in the third trimester at Polindes Mondokan was 18 people and a sample of 16 respondents. Simple random sampling technique and collection of pre-post test Hb data, McNemar statistical test. Result&Analysis : The results of the study using SPSS for windows with a significance level of = 0.005 obtained p value = 0.031. Discussion : It was concluded that there was an effect of giving added tablets of Fe and Ambon bananas to the increase in hemoglobin levels in pregnant women with anemia in the third trimester. Giving of Fe tablets together with Ambon Banana was more effective in increasing hemoglobin levels.